How rural is rural? The relationship between rural background of medical students and their career location intentions. (3rd June 2021) - Poole, Phillippa; Van Lier, Dylan; Verstappen, Antonia; Bagg, Warwick; Connell, Charlotte J.W.; Nixon, Garry; Wilkinson, Tim J.
Abstract: Objective: Rural background is associated with greater interest in rural practice. However, there is no universally agreed definition of 'rural' background used in medical school selection. This study explored the association between definitions of 'rural' background and students' intended career locations. Design: Prospective cohort study using survey data on career intention, hometown size, rurality of background, home address, high school and intended career location. Setting: University of Auckland, New Zealand (NZ). Participants: Commencing medical students 2009‐2017, inclusive. Main outcome measures: Univariate associations between student background according to 7 definitions of 'rural', and 3 definitions of intended practice location based on population size: urban intention (>100 000); regional intention (25 000‐100 000); rural intention (<25 000). Results: The sample size was 1592 students. 27.4% had a rural background by at least one definition. All definitions of rural background were associated with a greater rural intention. Applying a restrictive definition of rural (population<25 000) was associated with a higher likelihood of rural intention, but captured a smaller number of students. There was strong agreement between the population size of a student's background and intended practice location (chi‐square P < .0001). Conclusion: Rural intention varies by definition, but the number of students captured by each definition is important. Applying a binary or overly restrictive definition may limit interested students. Medical schools should adopt a definition of 'rural' that optimises the number of eligible students and their propensity to work rurally. Further, alternative ways of identifying students with rural intentions without a rural background should be explored.